A novel design of 8-Gbps IR-UWB pulse generator - Mohammed, Ahmed R.; Al-Khateeb, Khalid A. Saeed; Islam, Md. Rafiqul (2012)
In this paper, a novel design of 8 Gbps impulse radio ultra wideband (IR-UWB) pulse generator for short distances wireless communication is presented. The proposed pulse generator is based on 250 ps pulses, which gives advantages in pulse generation and detection error reduction. The generated pulses satisfy the regulations of UWB Federal Communication Commission (FCC) indoor and outdoor masks, while the pulse amplitude is 120 mVpp. The simple and efficient pulse generator is based on using four mixers with delay units working together with synchronized train of square pulses and sine wave power sources. The designed pulse generator utilizes on-off keying (OOK) and bi-phase modulation (BPM) techniques to increase the generator throughput speed. The design has been carried out using Advanced Design System (ADS) software.